Syringe exchange schemes for drug users in England and Scotland - Stimson, Gerry V (1988)
In 1987 experimental schemes for distributing injecting equipment to intravenous drug users to help prevent the spread of the human immunodeficiency virus were started by the government. After six months the schemes were found to have been reasonably successful in attracting clients but were less successful in keeping them. It has been shown that equipment can be distributed to drug users on an exchange basis. Many of the clients who were attracted to these schemes had had no treatment or other help for their drug problems.